The clinical manifestations and survival of systemic lupus erythematosus patients in Turkey: report from two centers - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2013)
Background Systemic lupus erythematosus (SLE) is a systemic autoimmune disease with a variety of clinical features. Survival has become longer as a result of better treatment modalities and better supportive care. There is no information on survival of SLE patients in Turkey. We evaluated clinical features and survival in SLE patients in two rheumatology departments. Methods All SLE patients being followed up by the Department of Rheumatology, Trakya University Medical Faculty, and the Department of Rheumatology, Marmara University Medical Faculty, over the 1996-2012 period were included. Patients were diagnosed with SLE if they fulfilled at least four American College of Rheumatology (ACR) criteria. The clinical and laboratory features, mortality data were obtained from medical charts. Results We had 428 SLE patients, and women (399 patients, 93.2%) far outnumbered men (29 patients, 6.8%). The mean age at the time of SLE diagnosis was 40.312.4 years. The most frequent clinical manifestations were arthritis (76.9%) and photosensitivity (70.1%). Renal disease was present in 32.9% of patients and neurological involvement in 12.9% of patients. After a median follow-up of 60 months, 19 patients died. The most frequent causes of death were ischemic heart disease, chronic renal failure and sepsis. The rate of five-year survival was 96%; 10-year survival, 92%; and 15-year survival, 88.8%. Multivariate Cox analysis showed that serositis at the time of diagnosis, SLE disease activity index (SLEDAI) score 6, and autoimmune hemolytic anemia were independent prognostic factors. Conclusions Data from two centers in Northwestern Turkey show that the mortality rate for SLE is similar to the rate in Western countries.
Keywords: Systemic lupus erythematosus; survival; prognosis; nephritis; PRIMARY ANTIPHOSPHOLIPID SYNDROME; ACCELERATED ATHEROSCLEROSIS; REVISED CRITERIA; MORTALITY; CLASSIFICATION; POPULATION; PREVALENCE; INDEX; RACE; SLE